A study on load balancing techniques in SDN - Ghosh, Anish; T. Manoranjitham, Mrs. (International Journal of Engineering and Technology, 2018)
Software defined networking(SDN) is a technique in networking which provides the administrators of the network with access to initialize, control, manage, and dynamically change how the network behaves through open interfaces and by the lower-level functioning abstraction. SDN simply addresses the basic knowledge that the architecture being static in traditional networks never provides assistance for the dynamic or scalable computing along along with the storage requirements of most of the modern computing. This is possible by the methods of decoupling or disassociation of the system that helps in making decisions about where the traffic is being delivered from the systems which then forwards this traffic to the required destination. Load balancing is the method in a computer network that is used to divide the amount of work between a collaboration of two or more computers in such a way that work can be completed in the same time limit. Hardware, software, or a combination of both can be used to implement load balancing. Moreover, computer server clustering is caused due to load balancing.This paper discusses the various kinds of load balancing algorithms which can help in better utilisation of resources and linear service delivery across multiple clients in an SDN environment.Â Â